Levinas's Modern Sacred - N. H. Smith (Law Text Culture, 2000)
Two concerns pervade Levinas's writings. The first is to persuade us that the basic ideas of monotheistic religion -- God, the transcendent, the infinite, and the holy -- are indispensible for understanding human subjectivity. The second is to rid these religious ideas of all metaphysical and theological impurity. One of the major sources of this impurity, in Levinas's view, is the traditional idea of the sacred. Levinas typically writes as if the very idea of the sacred were one of the chief obstacles to a proper understanding of religion. He denounces the sacred as "the essence of idolatry" (1990a: 14), as the "brother of sorcery" and "the half light" in which sorcery flourishes (1990b: 141). At other times, however, Levinas speaks of the sacred more positively, suggesting a contrast between a 'false', idolatrous sacred, and a 'true' sacred, one that expresses the authentic meaning of religion (1990a: 159, 1990b: 159). While it is true that Levinas is reluctant about using the word 'sacred' at all -- he prefers the expression "the holy" -- it makes sense to read him as rejecting not the concept of the sacred as such, but a particular metaphysical conception of it. That is to say, Levinas's reflections on the meaning of the basic concepts of monothesitic religion can be understood as a new way of thinking about the sacred, a way fitting for a modern, disenchanted, post-metaphysical age.